The Disparity Between Arbitration Award Number 01/LPS-PBJP/01/2024 and Kediri District Court Decision Number 56/Pdt.Sus-Arb/2024/PN Kdr on the Settlement of a Dispute over Green Open Space Land in the Kediri City Square - Nurbaedah (Al Qodiri : Jurnal Pendidikan, Sosial dan Keagamaan, 2026)
public procurement disputes because it directly affects legal certainty, contractual governance, and the finality of arbitration. This study aims to analyse and compare the legal reasoning adopted in Arbitration Award Number 01/LPS-PBJP/01/2024 and Kediri District Court Decision Number 56/Pdt.Sus-Arb/2024/PN Kdr concerning a dispute over the development of green open space land in Kediri City Square, with the objective of identifying the factors that produced divergent legal outcomes. The research employed a qualitative normative legal approach using both statute and case approaches. Primary legal materials consisted of relevant arbitration regulations and the two decisions under examination, while secondary materials included scholarly literature on arbitration, judicial review, and public procurement disputes. The findings reveal that both forums agreed that fault in contract management was shared by the contractor and the procuring authority. However, the arbitral tribunal annulled the contract termination and rejected the blacklist sanction, whereas the district court annulled the arbitral award after determining that the MC-50 progress recapitulation had not been adequately considered and that contractual changes should have been formally documented through a written addendum. The study concludes that the disparity between the two decisions originated not from conflicting factual findings but from differences in evidentiary assessment and contractual interpretation, highlighting the importance of evidentiary discipline and contractual documentation in preserving the practical finality of arbitration in Indonesian public procurement disputes.